Boosting electrochemical CO2 reduction on metal–organic frameworks via ligand doping - Dou, Shuo (2020)
Electrochemical CO2 reduction relies on the availability of highly efficient and selective catalysts. Herein, we report a general strategy to boost the activity of metal–organic frameworks (MOFs) towards CO2 reduction via ligand doping. A strong electron‐donating molecule of 1,10‐phenanthroline was doped into Zn‐based MOFs of zeolitic imidazolate framework‐8 (ZIF‐8) as CO2 reduction electrocatalyst. Experimental and theoretical evidences reveal that the electron‐donating nature of phenanthroline enables a charge transfer, which induces adjacent active sites at the sp2 C atoms in the imidazole ligand possessing more electrons, and facilitates the generation of *COOH, hence leading to improved activity and Faradaic efficiency towards CO production.